Lived Experiences, Challenges, and Coping Mechanisms of Teachers on the Current Paradigm Shift in Education: A Phenomenological Study - Risalita C. Nalla (Universal Journal of Educational Research)
This study employed an Interpretative Phenomenological Analysis (IPA) which aimed to explore the lived experiences, challenges, and coping mechanisms of teachers in the public school both in elementary and secondary schools in Malolos, Bulacan. The findings of this study revealed that most teachers are significantly challenged with the poor internet connection, multitasking and multitudes of paperwork to be submitted, communication with the parents and teachers and the different modalities of learning which are cited as the contributing factors of stress and anxiety. As to the experiences of the teachers, they became a module writer, online teacher, reporter while doing the online classes and juggling with the work at home as a homemaker. However, the good experiences of this pandemic brought realization to the teachers that they were able to unleash their potential and utilized the skills needed to survive in this difficult time. Moreover, teachers coped up with the situations through prayers, listening and watching motivational videos, yoga and others became farmers too just to avoid stress. Finally, the teachers also gave their suggestions to further help other teachers also who are struggling during this pandemic. Majority of the participants gave emphasis to focus on stabilizing mental health. Others also highlighted the need to seek the assistance of other people who are knowledgeable in terms of ICT. Continuing innovation and researching to update oneself was also one of the suggested ways to deal with the current paradigm shift in education.